High-efficiency generation of induced pluripotent stem cells from human foreskin fibroblast cells using the Sagunja-tang herbal formula - Ki Mo Kim; Deok Rim Heo; Joo Young Lee; Chang-Seob Seo; Sun-Ku Chung (BMC, 2017)
Abstract Background Sagunja-Tang (SGT-4) is a traditional herbal formula in Korean medicine that is used to treat anti-metabolic syndrome, and has antioxidant activity. In this study, we evaluated the effects of SGT-4 on the formation efficiency of induced pluripotent stem cells (iPSCs) from human foreskin fibroblasts (HFFs) by four reprogramming transcription factors: Oct4, Sox2, KIf4, and c-Myc (OSKM). Methods SGT-4 contained four different herbal medicines that are composed of Ginseng Radix, Glycyrrhizae Radix et Rhizoma, Atractylodis Rhizoma Alba, and Poria Sclerotium. The composition of SGT-4 was analyzed by high-performance liquid chromatography (HPLC). HFFs were transfected with episomal vectors contained by four OSKM. Western blotting, RT-PCR, immunofluroescence, and in vitro differentiation were used to assess the pluripotency of the iPSC cells. Results SGT-4 exhibited antioxidant activity against the generation of intracellular reactive oxygen species (ROS) as well as promoted the activation of superoxide dismutase 1 (SOD1), catalase, gluthathione peroxidase 1 (GPX1), and glutathione (GSH). Moreover, the ATP level was not significantly fluctuated depending on the concentration of SGT-4 in the hiPSCs. Conclusion Our results indicate that the SGT-4, herbal formula significantly increases the efficiency of human iPSC generation via the transcription factors (Oct4, Sox2, KIf4, and c-Myc).